Spin-dependent tunneling spectroscopy for interface characterization of epitaxial Fe/MgO/Fe magnetic tunnel junctions - Du, G; Wang, S; Ma, Q; Wang, Y; Ward, R; Zhang, X; Wang, C; Kohn, A; Han, X (2010)
Low-voltage spin-dependent tunneling spectroscopy of an epitaxial Fe/MgO/Fe magnetic tunnel junction is measured and compared to first-principles calculation of the tunneling conductance. The measured dynamic conductance (dI/dV) in the parallel configuration shows distinct asymmetric features as a function of the bias voltage. The peaks are independent of barrier thickness, magnetic field, and temperature. With the help of the first-principles calculations, positive and negative bias spectra can be related to different types of Fe/MgO interfaces. © 2010 The American Physical Society.